Perencanaan Sumber Daya Material pada Pekerjaan Arsitektur dengan Material Requerement Planning (MRP) pada Proyek Gedung Bertingkat - Muttaqin, Muh. Darul; Putra, I Nyoman Dita Pahang (Jurnal Talenta Sipil, 2024)
Construction in Indonesia is one of the government's top priorities in an effort to improve the welfare of the society. Construction planning must be carefully planned in order to achieve efficiency in project implementation, in terms of time and cost. A construction project requires planning and controlling material inventory. The purpose of material planning and control is so that construction projects can run smoothly, effectively and efficiently. Material planning and control can be analyzed using the material requirements planning (MRP) method. In this study, using economic order quantity (EOQ) and period order quantity (POQ) techniques. Cost budget design data, s-curves, work unit price analysis, and work progress reports are the data components to be processed. The results showed the cost of procurement of materials needed with the EOQ technique, namely: purchase cost of IDR 8,466,623,718.49, ordering cost of IDR 1,598,050.00, and storage cost of IDR 8,942,979.62. The total cost required is IDR 8,477,164,748.11. Furthermore, for the POQ technique, namely: purchase cost of IDR 8,466,623,718.49, ordering cost of IDR 1,598,050.00 and storage cost of IDR 9,674,554.05. The total cost required is IDR 8,477,896,322.53 Comparison of the costs required from the EOQ and POQ techniques can be concluded that Material Requirement Planning (MRP) using the Economic Order Quality (EOQ) technique is less costly than the Period Order Quantity (POQ) technique. Material procurement using Economic Order Quality (EOQ) is more effective. This is because the EOQ technique requires less costly / economic procurement compared to the POQ technique. In addition, with the application of the EOQ technique, there is a clearer material ordering schedule and the amount of material ordered is in accordance with the needs so that the material storage is not too much.